Successful aging: The role of cognitive gerontology. Issue 1 (1st January 2018) - Hartley, Alan; Angel, Lucie; Castel, Alan; Didierjean, André; Geraci, Lisa; Hartley, Joellen; Hazeltine, Eliot; Lemaire, Patrick; Maquestiaux, François; Ruthruff, Eric; Taconnat, Laurence; Thevenot, Catherine; et al.
ABSTRACT: This commentary explores the relationships between the construct of successful aging and the experimental psychology of human aging—cognitive gerontology. What can or should cognitive gerontology contribute to understanding, defining, and assessing successful aging? Standards for successful aging reflect value judgments that are culturally and historically situated. Fundamentally, they address social policy; they are prescriptive. If individuals or groups are deemed to be aging successfully, then their characteristics or situations can be emulated. If an individual or a group is deemed to be aging unsuccessfully, then intervention should be considered. Although science is never culture-free or ahistorical, cognitive gerontology is primarily descriptive of age-related change. It is not prescriptive. It is argue that cognitive gerontology has little to contribute to setting standards for successful aging. If, however, better cognitive function is taken as a marker of more successful aging—something not universally accepted—then cognitive gerontology can play an important assessment role. It has a great deal to contribute in determining whether an individual or a group evidences better cognitive function than another. More importantly, cognitive gerontology can provide tools to evaluate the effects of interventions. It can provide targeted measures of perception, attention, memory, executive function, and other facets of cognition that are more sensitive to change than most clinical measures. From a deep understanding of factors affecting cognitive function, cognitive gerontology can also suggest possible interventions. A brief narrative review of interventions that have and have not led to improved cognitive function in older adults. Finally, the enormous range is addressed in the estimates of the proportion of the population that meets a standard for aging successfully, from less than 10% to more than 90%. For research purposes, it would be better to replace absolute cutoffs with correlational approaches (e.g., Freund & Baltes, 1998, Psychology and Aging, 13, 531–543). For policy purposes, cutoffs are necessary, but we propose that assessments of successful aging be based not on absolute cutoffs but on population proportions. An example of one possible standard is this: Those more than 1 standard deviation above the mean are aging successfully ; those more than 1 standard deviation below the mean are aging unsuccessfully ; those in between are aging usually . Adoption of such a standard may reduce the wide discrepancies in the incidence of successful aging reported in the literature.